Hormonal contraceptives do not impact economic preferences: Evidence from a randomized trial - Ranehill, Eva; Zethraeus, Niklas; Blomberg, liselott; von Schoultz, Bo; Hirschberg, Angelica Lindén; Johannesson, Magnus; Dreber, Anna (Management Science, 2018)
A growing body of correlational studies suggests that sex hormones such as those contained in, or affected by, oral contraceptives (OCs) may impact economic behavior. However, despite widespread use of OCs among women in Western countries, little is known about their potential behavioral effects. The present study investigates whether OCs causally influence economic preferences. We randomly allocate 340 women aged 18–35 to three months of a widely used OC or placebo treatment. At the end of treatment, we conduct an economic experiment measuring altruism, financial risk taking, and willingness to compete. The statistical power is 80% to detect an effect size equal to a Cohen’s d of 0.30 at the 5% level. We find no significant effects of OCs on any of the measured preferences, indicating that this widely used OC treatment, commonly used throughout the world, does not significantly affect the measured economic preferences. Further, we find no relation between menstrual cycle phase and economic preferences in the placebo group.